The Effects of Global, Regional, and Local Macroeconomic Events on the Price of the Colombian Castilla Blend - Cayon, Edgardo; Garzon, Natalia Andrea; Perez, Juan Sebastian (International Journal of Energy Economics and Policy, 2019)
The Castilla blend is a heavy crude produced in the plain fields of Colombia and is similar to the heavy crudes produced in other countries in the Western hemisphere. One characteristic of this type of crude is that it is sold at a discount rate that can oscillate between a 4- and 10-dollar discount from benchmark indices such as the Intercontinental Exchange (ICE) Index and the West Texas Intermediate (WTI) Index. In the present study, we used event study methodology to determine the impact of global, regional, and local macroeconomic news, as well as the Organization of the Petroleum Exporting Countries (OPEC) announcements on the Castilla blend price. We found that even though OPEC announcements have a higher impact on prices, macroeconomic news that comes as a surprise from global and regional players had a significant impact on the Castilla blend price for the period under study from 2010 to 2019. Keywords: Oil, Colombia, macroeconomic events. JEL Classifications: G1, G14 DOI: https://doi.org/10.32479/ijeep.8220